Are hospitals with both medical/surgical and psychiatric services associated with decreased difficulty in ambulance transfer for patients with self-harm behaviour? A nationwide retrospective observational study using ambulance transfer data in Japan. Issue 2 (24th February 2023) - Chiba, Takuyo; Takaku, Reo; Ito, Erina; Tamune, Hidetaka; Rivera, Marisa; Ikeda, Shunya; Shiga, Takashi
Abstract : Objectives: Ambulance diversion and prolonged prehospital transfer time have a significant impact on patient care outcomes. Self-harm behaviour in particular is associated with difficulty in hospital acceptance and longer prehospital transfer time. This study aimed to determine if hospitals with both medical/surgical and psychiatric inpatient beds and high-level emergency care centres are associated with a decreased rate of difficulty in hospital acceptance and shorter prehospital transfer time for patients seeking medical care after self-harm behaviour. Design and setting: A retrospective observational study using the database of Japanese ambulance dispatch data in 2015. Participants: Patients who were transferred by ambulances after self-harm behaviour. Interventions: None. Main outcome measures: Multivariable logistic regression analysis and multivariable linear regression analysis were performed to assess whether the presence of hospitals with both medical/surgical and psychiatric inpatient beds and high-level emergency care centres in the city were associated with a decreased rate of difficulty in hospital acceptance and shorter prehospital transfer time. Results: The number of transfers due to self-harm behaviour in 2015 was 32 849. There was an association between decreased difficulty in hospital acceptance and the presence of high-level emergency care centres (OR 0.63, 95% CI 0.55 to 0.71, p<0.01) and hospitals with both medical/surgical and psychiatric inpatient beds (OR 0.50, 95% CI 0.38 to 0.66, p<0.01). There was a significant reduction in prehospital transfer time in the city with high-level emergency care centres (4.21 min, 95% CI 3.53 to 4.89, p<0.01) and hospitals with medical/surgical and psychiatric inpatient beds (3.46 min, 95% CI 2.15 to 4.77, p<0.01). Conclusion: Hospitals with both medical/surgical and psychiatric inpatient beds and high-level emergency care centres were associated with significant decrease in difficulty in hospital acceptance and shorter prehospital transfer time.